Mystery of a missing Cu-T: a case report - Tiwari, Ajiti; Hiremath, P. B.; Indu, N. R.; Jayashree; Shaheen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The Cu-T intrauterine device (IUD) is a popular contraceptive method. However, a "missing" Cu-T IUD poses a clinical challenge. This situation arises when the IUD cannot be visualized on ultrasound or X-ray, raising concerns about potential complications. This review discusses the etiology, diagnosis, and management of a missing Cu-T IUD, including the role of imaging modalities, surgical interventions, and patient counseling. This case report aims to discuss the complications and consequences of a "missing Cu-T" IUD, including perforation, migration, and infertility. We examine the causes, diagnosis, and management of this condition, highlighting the importance of timely detection and appropriate intervention to prevent long-term consequences.